Crowding perception: A case study of developed systematic literature review procedure with multiple software programs as management and synthesis tools - B, Alsolami; M R, Emb (International Journal of Engineering and Technology, 2018)
The aim of this paper is to presents a case study that implements a proposed procedure for conducting a systematic literature review (SLR). The case study is in the field of crowding perception. Following the traditional data processing model, the proposed procedure consists of seven stages: 1) planning the review, 2) conducting the review, 3), organization and preparation for synthesis, 4) actual coding, 5) data extraction & organization, 6) data synthesis, and 7) reporting the review. In addition, the proposed procedure includes the usage of four software programs as supporting tools. The paper includes detailed steps on how each stage has been implemented to systematically review the crowding perception literature. The proposed SLR procedure and the case study presented in this paper offer an effective process of literature review. A specific contribution of this study to SLR is expanding the tools usage to include other software programs.Â